Job matching across occupational labour markets - Michael Stops (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2012)
This paper refers to an analysis of matching processes in occupational labour markets in terms of classes of jobs that share extensive commonalities in their required qualifications and tasks. To date, all studies in this field have been based on the assumption of separate occupational labour markets. This assumption suggests that job search and matching processes only transpire within distinct occupational labour markets and that no occupational changes occur. I present theoretical and empirical arguments that undermine the validity of this assumption. Moreover, I construct an occupational topology based on information about the ways in which occupational groups may be seen as alternatives in searches for jobs or workers respectively. I then use pooled ordinary least squares, fixed effects, and pooled mean-group models that consider cross-sectional dependency lags for regressors to test the hypothesis that job search and matching occur across occupational labour markets. In particular, I find significant and positive matching elasticities with respect to the averaged numbers of unemployed workers and vacancies in similar occupational groups; these results clearly support my hypothesis. Furthermore, there are indications that returns to scale that are derived from the results of the pooled mean-group model are constant. The findings of this study strongly suggest the use of an augmented matching function that considers job and worker searches across occupational labour markets. – – Dieses Papier befasst sich mit der Analyse von makroökonomischen Matchingfunktionen auf beruflichen Teilarbeitsmärkten. Allen bisher hierzu vorliegenden Papieren lag die Annahme zugrunde, dass berufliche Teilarbeitsmärkte abgeschottet voneinander sind und somit berufliche Mobilität nicht vorliegt. Ich präsentiere einige theoretische und empirische Belege gegen diese Annahme. Auf der Grundlage von Informationen darüber, welche Berufsgruppen bezogen auf die Arbeitssuche bzw. die Rekrutierung von Arbeitskräften Alternativen darstellen, konstruiere ich eine Berufstopologie. Mit deren Hilfe teste ich die Hypothese der Durchlässigkeit der beruflichen Teilarbeitsmärkte. Dabei verwende ich Pooled OLS-, Fixed-Effects- und Pooled-Mean-Group-Schätzer und modelliere die Durchlässigkeit als Abhängigkeiten der jeweiligen Neueinstellungen in einer Berufsgruppe vom durchschnittlichen Bestand der Arbeitslosen und Vakanzen in ähnlichen Berufsgruppen. Es ergeben sich signifikant positive Matchingelastizitäten von Arbeitslosen und Vakanzen in ähnlichen Berufsgruppen und damit wird die beschriebene Hypothese auch empirisch gestützt. Des Weiteren bieten die Ergebnisse Indizien dafür, dass die Skalenerträge, die sich aus dem Pooled-Mean-Group-Modell ergeben, konstant sind. Alles in allem zeigen die Ergebnisse deutlich, dass bei der Modellierung und Schätzung von Matchingfunktionen berücksichtigt werden sollte, dass die Prozess der jeweils individuellen Job- bzw. Bewerbersuche häufig nicht nur auf einem sondern über mehrere berufliche Teilarbeitsmärkte ablaufen.
Keywords: C21; C23; J44; J64; 330; Unemployment; Vacancies; Matching Model; Panel Data; Occupational Labour Markets